Optimizing agricultural insurance to meet the demands of farmers: Evidence from India - Ghosh, Ranjan Kumar; Gupta, Shweta; Singh, Vartika; Ward, Patrick S. (Agricultural and Applied Economics Association, 2019)
Researchers and policymakers have long understood the benefits of crop insurance, but have been consistently disappointed by the poor performance of these programs. Rarely have programs seen sizeable take-up rates without support through large government subsidies, and in many countries demand has been meager even at prices well below fair-market rates. Experiences from India have largely followed this trend, despite a number of large policy initiatives. Limited demand stems from low perceived value, arguably because the existing insurance products are unsuited to farmers’ needs. The present study fills an important gap by demonstrating that incorporating product characteristics better suited to farmers’ preferences can lead to higher take-up. To do so, we conducted a discrete choice experiment with agricultural households in four states in India. While farmers seem to like several of the features of policies offered under existing programs, our results suggest they would generally be willing to pay more as premium than the current highlysubsidized rates, in return for more assured and timely payouts.